Performance analysis of employees at the Nabire District Land Office - Worabay, Errick; Maharani, Anita; Riana, Kurnia Endah (Privietlab, 2024)
This research aims to understand the correlation and determination of factors that have an impact on improving employee performance, especially regarding the cor- relation and determination Research information was collected by administering a questionnaire to identify respondents, especially the employees of the Nabire Re- gency Land Office. In this study, 42 questionnaires were distributed to 42 partici- pants. 42 duplicate surveys were returned, resulting in a reaction rate of 100.0%. The results of the study show that the majority of respondents assessed the work ability, motivation, facilities, and performance of district land office employees. Nabire is Very High. The variables work ability, work motivation, and work facilities have a joint influence on the performance of Nabire Regency Land Office Employees